Risk management behaviour of banana growers - Ranjana Damodaran T (Department of Agricultural Extension, College of Horticulture, 1994)
The study was undertaken in selected give panchayaths of Thrissur district, to analyse the extent of risk management behavior of banana growers in relation to their attitude and perception about risk in banana cultivation. The respondents selected for the study included both summer banana cultivators (n=120) and Kazhchakula cultivators (n=30).